Duopoly: Value Where Sellers are Few - C., E. H. (Quarterly Journal of Economics, 1929)
The problem stated and limited, 63. — The result when sellers consider only their direct influence upon price and adjust amounts (Cournot), 66. — The same when prices are adjusted (Bertrand, Marshall, Pareto, Edgeworth, Pigou), 69. — The result when sellers consider their total influence upon price, 83. — The factor of uncertainty as to what the other seller will do, 87. — The effects of '#|201C;friction,” 89. — Summary, 91. Mathematical Appendix, 93. — Cournot, 93. — Pareto, 95. — Amoroso, 97. — Evans, 97> — Bowley, 98.